Deep Learning Based Flipbook Media to Improve Descriptive Text Learning in Elementary Schools - Khasanah, Siti Nur; Majid, Akbar Al (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the effectiveness of a deep-learning approach assisted by flipbook media in improving Indonesian language learning outcomes on descriptive-text material for elementary students. The research involved 22 fifth-grade students at SD Negeri Salamrejo, Kulon Progo. A quantitative one-group pretest-posttest pre-experimental design was employed, with data collected through a validated multiple-choice test. Analysis included normality and homogeneity tests, Pearson correlation, paired-sample t-test, and normalized gain (N-Gain). The findings indicate a strong positive correlation between pretest and posttest scores (r = 0.884, p < 0.001), a significant mean difference (t = –15.11, p < 0.001, 95% CI [–20.17, –15.29]), and an average N-Gain of 0.55, classified as medium improvement. Notably, these findings confirm that integrating deep-learning pedagogy with flipbook media strengthens students' conceptual understanding, critical reflection, and higher-order thinking in descriptive-text learning. The results provide practical guidance for teachers to incorporate interactive flipbook-based activities that foster reflective discussion, contextual examples, and peer feedback, thereby enriching classroom practices and supporting the development of 21st-century literacy skills.